2008
DOI: 10.1080/00222340802118259
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Dynamics ofl‐Proline‐l‐Hydroxyproline: A Fragment of Collagen

Abstract: Normal mode studies are reported for L-proline L-hdroxyproline, a fragment of collagen. A comparision of amide I mode in peptide with that in collagen shows the presence of such sequences in collagen. Other possible sequences show appreciable differences, and hence they are not likely to be present in large numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The two weak bands between 2800 and 2900 cm –1 observed for the collagen sample have not been clearly assigned to specific vibrational modes in the literature. In FT IR spectral analysis of a collagen model dipeptide, l -prolyl- l -hydroxyproline, some peaks below 2900 cm –1 were reported under the CH 2 ring modes without clear attributions . The proline and hydroxyproline residues have CH groups on C α , and the stretching mode may contribute to the VR SFG spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two weak bands between 2800 and 2900 cm –1 observed for the collagen sample have not been clearly assigned to specific vibrational modes in the literature. In FT IR spectral analysis of a collagen model dipeptide, l -prolyl- l -hydroxyproline, some peaks below 2900 cm –1 were reported under the CH 2 ring modes without clear attributions . The proline and hydroxyproline residues have CH groups on C α , and the stretching mode may contribute to the VR SFG spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…In FT IR spectral analysis of a collagen model dipeptide, Lprolyl-L-hydroxyproline, some peaks below 2900 cm −1 were reported under the CH 2 ring modes without clear attributions. 62 The proline and hydroxyproline residues have CH groups on C α , and the stretching mode may contribute to the VR SFG spectrum. In previous VR SFG studies of polymers, some peaks observed in 2850−2910 cm −1 range were assigned to the CH stretch.…”
Section: ■ Results and Discussionmentioning
confidence: 99%